Effects of gas and droplet characteristics on drop-drop collision outcome regimes. (December 2015) - Krishnan, K.G.; Loth, E.
Highlights: Robust models for droplet outcomes that includes droplet viscosity and gas effects. We propose the first ever model SC/B boundary. We propose a model for B/FC that incorporates gas density effects. We compile all available experimental data on droplet collisions. Abstract: Droplet-droplet collisions occur in many spray systems. The collision of two spherical droplets in a gas is considered in terms of the five primary phenomenological outcomes: slow coalescence (SC), bounce (B), fast coalescence (FC), reflexive separation (RS), and stretching separation (SS). The boundaries that separate these outcomes were investigated herein in terms of droplet viscosity and surface tension as well as gas pressure and density. Gas effects are not accounted for previous models, but can be important for hydrocarbon drops in pressurized sprays associated with many fuel systems. Based on a comprehensive review of available drop-drop collision data, phenomenological models were proposed herein for a wide variety of test conditions. For slow coalescence/bouncing (SC/B), increasing droplet viscosity and gas pressure were found to increase the probability of a bouncing outcome of the collision. For the B/FC boundary, increasing droplet viscosity and gas density were also found to increase bouncing probability. In both cases, the variations can be explained in terms of the stability of the gas layer that develops between the droplets. Additionally, the Brazier-Smith model for the FC/SS boundary was modified to increase robustness for a wide range of droplet viscosities. In general, the present models reasonably predicted collision outcomes for a large variety of gas pressures and densities as well as droplet viscosities and surface tensions. These are also the first models to include gas effects and the first models of the SC/B boundary. However, the droplet diameters of the data set were limited in range from 200 to 400 microns. Significantly larger droplet collisions may include effects on initial non-sphericity while significantly smaller drop collisions may include effects on non-continuum flow and gas viscosity.